Female Leadership and Gender Gap within Firms: Evidence from an Italian Board Reform. (March 2022) - Maida, Agata; Weber, Andrea
The authors evaluate a 2011 Italian law that installed a step-wise increase in gender quota that remains effective for three consecutive board renewals of listed limited liability firms. They link firm-level information on board membership and board election dates with detailed employment and earnings records from the Social Security registers. Exploiting the staggered introduction of the gender quota regulation and variation in board renewal years across firms, the authors evaluate the effect of the board gender composition on measures of gender diversity in top positions over a period of four years. While the reform substantially raised the female membership on corporate boards, results show only moderate and imprecisely estimated spillover effects on the representation of women in top executive or top earnings positions.